The Government's Responsibility in Resolving Contract Disputes Between Pharmacy Facility Owners and Pharmacists - Deny Sulistiyowati; Mohammad Zamroni; Andika Persada Putera (Jurnal Indonesia Sosial Sains, 2025)
Contract disputes between owners of pharmaceutical facilities (PSAs) and pharmacists in charge (APAs) often arise due to an imbalance in the rights and obligations stipulated in cooperation agreements. These contracts are often onerous for pharmacists, such as requiring them to find a replacement before resigning, without providing adequate protection. In some cases, pharmacists do not even receive the salary to which they are entitled. This research aims to analyze the legal protections available to pharmacists facing contract disputes and the government's responsibility in resolving such issues. This research uses a normative legal study method with statutory and conceptual approaches. The research findings show that legal protection for pharmacists is divided into two aspects: internal (through contracts) and external (through government regulations). However, many contracts do not have adequate dispute resolution mechanisms, and the implementation of government responsibilities is still not optimal. The study concludes that there is a need to improve cooperation agreements between PSAs and APAs by adopting the principles of equality and fairness. The government should improve supervision and law enforcement to protect pharmacists from violations of their rights. In addition, dispute resolution mechanisms, both litigation and non-litigation, should focus more on efficiency and effectiveness.